Improvement of Repair Service Quality Using Service Quality and Quality Function Deployment Methods (Case Study at UD Dua Teknik ASC PT LG Electronics) - Jihan Pradesi; Ramy Yahya; Muhammad Miftakul Anwar (International Journal of Seocology, 2021)
Authorized service center is an authorized service center appointed and approved by the main party. UD Dua Teknik is a business engaged in electronic repair and maintenance services that focuses on products owned by PT LG Electronics. This research was conducted to improve the service of UD Dua Teknik using the Servqual method and quality function deployment. The research shows that the dimensions of reliability and responsiveness have the largest gap and variables that can be pursued are appearance, service, handling, response speed. Based on the results of the preparation of the House of Quality, the proposed improvement is to provide training on all aspects.